Pengaruh Firm Size, Political Connection, Gender Diversity, Profitability, dan Leverage Terhadap Water Disclosure pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2021-2022 - Hasibuan, Nurmalatipah; Ismail, Mutia (Universitas Batanghari Jambi, 2024)
This study aims to determine firm size on water disclosure, the effect of political connection on water disclosure, the effect of gender diversity on water disclosure, the effect of profitability on water disclosure, and the effect of leverage on water disclosure in mining sector companies listed on the Indonesia Stock Exchange for the period 2021-2022. The research sample was 47 mining companies, using purposive sampling technique. Data analysis method with multiple linear regression. The results of this study indicate that, the firm size variable has no effect on water disclosure, the political connection variable has a significant positive effect on water disclosure, the gender diversity variable has no effect on water disclosure, the profitability variable has no effect on water disclosure, and the leverage variable has a significant negative effect on water disclosure. Simultaneously, the firm size variable, political connection, gender diversity, profitability, and leverage affect water disclosure.